Label matters: how labeling and diagnosis affect lay perception of people with depressive symptoms - Kulwicka, Katarzyna; Rusowicz, Jagoda; Gasiorowska, Agata (Frontiers in Psychiatry, 2025)
We investigated how the label “depression” and information about a medical diagnosis influence perceptions of individuals with depressive symptoms as legitimately experiencing depression and a medical condition. In three experiments, participants read a description of a person meeting Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria for major depressive episode and manipulated whether the label “depression” and the information about a professional medical diagnosis were included. Participants were more likely to perceive the person as having depression when both the label and diagnosis were present. However, paradoxically, when a diagnosis explicitly included the word “depression”, participants were less likely to view the symptoms as indicating a legitimate medical condition than when the diagnosis omitted the term. These effects were not moderated by participants’ own experience of depression. Gender effects emerged in Experiment 3: results replicated for male protagonists but differed for female protagonists, where label effects were independent of medical diagnosis information. Finally, a meta-analysis across the three experiments supported our hypothesis that the label “depression” weakened the effect of the medical diagnosis. Moreover, participants attributed a higher degree of legitimacy to a medical condition when the diagnosis was provided by a doctor, but only when this diagnosis did not include the label “depression”.